2024
DOI: 10.1093/mnras/stae040
|View full text |Cite
|
Sign up to set email alerts
|

Panchromatic (Sub)millimeter polarization observations of HL Tau unveil aligned scattering grains

Zhe-Yu Daniel Lin,
Zhi-Yun Li,
Ian W Stephens
et al.

Abstract: Polarization is a unique tool to study the dust grains of protoplanetary disks. Polarization around HL Tau was previously imaged using the Atacama Large Millimeter/submillimeter Array (ALMA) at Bands 3 (3.1 mm), 6 (1.3 mm), and 7 (0.87 mm), showing that the polarization orientation changes across wavelength λ. Polarization at Band 7 is predominantly parallel to the disk minor axis but appears azimuthally oriented at Band 3, with the morphology at Band 6 in between the two. We present new ∼0.2″ (29 au) polariza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…Here α = 0.1 is used to produce the small polarization degree of ∼2% as observed in the disk, which is optically thick in Band 7 and thus expected to have a polarization fraction significantly reduced from the maximum value. Interestingly, a similar α value has been adopted to reproduce the polarization images of HL Tau observed from ALMA Band 7 (Stephens et al 2023) to the VLA Q band (Lin et al 2024).…”
Section: Magnetically Aligned Grainsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here α = 0.1 is used to produce the small polarization degree of ∼2% as observed in the disk, which is optically thick in Band 7 and thus expected to have a polarization fraction significantly reduced from the maximum value. Interestingly, a similar α value has been adopted to reproduce the polarization images of HL Tau observed from ALMA Band 7 (Stephens et al 2023) to the VLA Q band (Lin et al 2024).…”
Section: Magnetically Aligned Grainsmentioning
confidence: 99%
“…In particular, the dust polarization due to dust self-scattering is affected by the asymmetry in the flux incoming from various directions, while the dust polarization due to the magnetically aligned grains is not. Recent dust polarization observations toward the well-studied HL Tau disk at a submillimeter wavelength of 870 μm have indeed shown that the rings and gaps in the disk have different polarization degrees and orientation, which can be attributed to both scattering and emission from the aligned grains (Stephens et al 2023;Lin et al 2024).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HL Tauʼs polarization spectrum is particularly interesting: the diskʼs polarization morphology transitions from a pattern consistent with scattering at ∼870 μm to an elliptical pattern at ∼3 mm, with an intermediate pattern at ∼1.3 mm (Stephens et al 2017). Recently, Lin et al (2022) and Lin et al (2024) have demonstrated that HL Tauʼs polarization spectrum could be explained by polarization from thermal emission and the scattering of aligned grains, also demonstrating that the polarization seen at high resolution in HL Tau at 870 μm could be explained by the same mechanisms. At longer wavelengths, thermal polarization dominates because the low optical depth makes scattering inefficient.…”
Section: Introductionmentioning
confidence: 99%